2010
DOI: 10.1097/olq.0b013e3181d13eed
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis and HIV Seroconversion Among a 12-Month Prospective Cohort of Men Who Have Sex With Men in Shenyang, China

Abstract: Background Cross-sectional studies have found a high prevalence of syphilis and HIV infection among men who have sex with men (MSM) in China. Methods A total of 218 HIV-negative MSM participated in this prospective cohort study. Interviewer-administered questionnaires were completed, and blood samples were obtained for HIV and syphilis testing, both upon enrollment and at 12-month follow-up. Results Of enrolled participants, 56% (122) were retained for the full 12-month follow-up period. The cohort had an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 24 publications
8
107
4
Order By: Relevance
“…Incidence conveys information about the risk of contracting the disease, whereas prevalence indicates the distribution of the disease. Previous studies revealed both high HIV incidence and high HIV prevalence among MSM in Shenyang (12)(13)(14). Currently, HIV, syphilis, and gonorrhea are notifiable by law in China; however, genital herpes caused mainly by HSV-2, is not.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence conveys information about the risk of contracting the disease, whereas prevalence indicates the distribution of the disease. Previous studies revealed both high HIV incidence and high HIV prevalence among MSM in Shenyang (12)(13)(14). Currently, HIV, syphilis, and gonorrhea are notifiable by law in China; however, genital herpes caused mainly by HSV-2, is not.…”
Section: Introductionmentioning
confidence: 99%
“…23,29 Whereas previous research provides only cross-sectional data on the incidence rates of HIV, syphilis and hepatitis B virus (HBV) infections, 9,13,30-32 a limited number of cohort studies with small sample sizes and/or poor retention rates among MSM were conducted recently in China. 33,34 This is the first cohort study among MSM in China to assess the correlates of HIV, syphilis, and HBV seroconversions among this group in Beijing.…”
mentioning
confidence: 99%
“…7,8 Similar trends for MSM have been observed throughout Europe 9 and China. 3,10,11 Some reports suggest that the increasing incidence of syphilis may be due to high-risk behaviours, such as methamphetamine use, 12-14 but as we will discuss later, the higher rates of syphilis and HIV coinfection may also be due to immunological factors.…”
Section: Syphilis Neurosyphilis and Hivmentioning
confidence: 99%